Analisis Tingkat Partisipasi Masyarakat dalam Pencegahan Penyebaran Covid-19 di Wilayah Kerja Puskesmas Biru Kab. Bone - Kistan; Najman (STIKes Payung Negeri Pekanbaru, 2021)
Introduction: Based on the prevention of the spread of COVID-19, it is not only the responsibility of the government but all components of society, both arising from their own awareness and seeing the benefits principle. A total of 397 people in the Blue Health Center working area consisting of 8 sub-districts became respondents in this study. The sampling technique used is simple random sampling. Data collection using questionnaires. Methods: The method used is descriptive quantitative method, with descriptive statistical analysis techniques and Spearman rank correlation analysis. Results: The results of the analysis show that community participation in the Blue Health Center work area starts from community involvement in planning (0.466) by being involved in socialization and agreeing with the implementation of health protocols, community involvement in implementation (0.599) by implementing physical distancing, self-quarantine and self-isolation health protocols, community involvement in receiving benefits (0.477) by feeling safe if applying health protocols and community involvement in supervision (2.57) by supervising each other between residents to comply with health protocols and reporting if there are outsiders who enter the community environment or by monitoring the recommended community for self-isolation or there are residents who are confirmed or not COVID-19. Conclution: From the results of the Spearman Correlation Test, it was found that community participation has a fairly strong relationship with preventing the spread of COVID-19, namely the higher the level of community participation, the higher the prevention of the spread of COVID-19.